122 Penthrox: a service evaluation for methoxyflurane use in an emergency department setting. Issue 12 (23rd November 2020) - Ingham, Jack; Roberts, Gareth
Abstract : Aims/Objectives/Background: In Manchester Royal Infirmary, a major trauma centre, there are many patient presentations which require fast acting analgesia. Often these presentations, such as shoulder dislocations, require conscious sedation in order to be safely, effectively and humanely treated. Penthrox was introduced to the emergency department in December 2019. It was hoped that it would be used as an alternative to conscious sedation in patients requiring procedures. It was postulated that by having another analgesic method available, patients would have a greater likelihood of being discharged without the requirement for conscious sedation. This would therefore not require waiting for a Resus bed and therefore reduce length of stay in the department. Methods/Design: Data was prospectively gathered for patients who received Penthrox in the months of December 2019 to July 2020 using a questionnaire that was filled in by clinicians. Audit forms were collated as well as attendance data (including length of stay) for shoulder dislocations Dec 19 - Feb 19. Pain scores were subjectively scored out of 10 and, using t-tests, compared for significance. Length of stay, checklist completion, progression to concious sedation, further pain relief requirements and indications were also analysed. Results/Conclusions: Subjectively reported pain scores were significantly reduced when comparing before and during procedure (<0.001, 95% CI of a reduction of 1.959 to 5.113) and also before and 10 mins after procedure (p= <0.001, 95% CI 3.96 to 6.33). The distributions of pain scores are demonstrated in the violin plot below. There was no significant association between checklist completion and progression to concious sedation. Difference between length of stay did not quite meet statistical significance (mean = 163.62 using penthrox, mean = 225 without penthrox. p = 0.06). There were no significant adverse events. In conclusion Penthrox is a safe and welcome addition to the ED formulary.